The Hybrid Classroom’s Challenges of Senior High School Students Learning - Zulfi Yuniar (Universitas PGRI Adi Buana Surabaya, 2023)
The study aims to discover challenges in hybrid learning in senior high school. As a researcher, the researcher will conduct this research to learn about the challenges that exist in hybrid learning. This research design is qualitative approaches. This understanding refers to the experience of students who have attended a hybrid class. This study used a qualitative method, and the researcher used a case study. This research will only apply interviews to collect the primary data. The researcher constructs blueprint interviews and guidelines to mine reliable and valid data. The data taken from this study is in the form of an in-depth interview statement. The data source was one student each from 4 high schools. In this study, structured interviews were used as a data collection approach. Thematic analysis was used to analyse the data in this study. This study found five challenges that students face in online learning. These challenges are obstacles in accessing the application and internet connection problems that often occur when learning online. Other challenges are less interaction between students and teachers in the online classroom. In addition, there are difficulties in understanding the material during online learning. Students also have problems related to unclear pronunciation during online learning. This study also found two challenges students face in offline education: fewer sources and less technology.